2022
DOI: 10.1002/ajh.26689
|View full text |Cite
|
Sign up to set email alerts
|

Low‐dose dasatinib 50 mg/day versus standard‐dose dasatinib 100 mg/day as frontline therapy in chronic myeloid leukemia in chronic phase: A propensity score analysis

Abstract: Low‐dose dasatinib is safe and effective in patients with chronic myeloid leukemia in chronic phase (CML‐CP). No randomized trials have compared the outcome with standard‐dose dasatinib. This study aims to compare the outcome of patients with CML‐CP treated with frontline dasatinib 50 versus 100 mg/day. We analyzed 233 patients with newly diagnosed CML‐CP treated with low‐dose dasatinib (N = 83) or standard‐dose dasatinib (N = 150). Propensity score analysis with 1:1 matching was performed and identified 77 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 23 publications
(54 reference statements)
1
17
0
Order By: Relevance
“…Obviously, the presence of ABL1 mutations, such as T315I, dictates a more specific mutation‐targeted approach, our current preference being ponatinib. In the current issue of AJH , Jabbour and colleagues from MD Anderson Cancer Center (MDACC) share their experience in using dasatinib at either 50 or 100 mg/day, for frontline therapy in CML‐CP 19 . The authors used propensity score analysis to compare the two doses among 154 patients (77 for each dose level) selected from a cohort of 233.…”
Section: Imatinib (Gleevec®) Dasatinib (Sprycel®) Nilotinib (Tasigna®...mentioning
confidence: 99%
See 3 more Smart Citations
“…Obviously, the presence of ABL1 mutations, such as T315I, dictates a more specific mutation‐targeted approach, our current preference being ponatinib. In the current issue of AJH , Jabbour and colleagues from MD Anderson Cancer Center (MDACC) share their experience in using dasatinib at either 50 or 100 mg/day, for frontline therapy in CML‐CP 19 . The authors used propensity score analysis to compare the two doses among 154 patients (77 for each dose level) selected from a cohort of 233.…”
Section: Imatinib (Gleevec®) Dasatinib (Sprycel®) Nilotinib (Tasigna®...mentioning
confidence: 99%
“…It was also pointed out by the authors that among the 77 patients in the dasatinib 50 mg daily cohort, only 2 (3%) patients required dose escalation to dasatinib 100 mg/day, for suboptimal response ( Koji Sasaki, personal communication 8/17/2022 ). The authors stated that low‐dose dasatinib (50 mg/day) was the standard of care at their institution for newly‐diagnosed CML‐CP 19 . In line with this experience from MDACC, a recent study from Japan reported on 52 TKI‐naïve older CML‐CP patients (median age 78 years, range 74–83) treated with dasatinib at 20 mg/day; at a median follow‐up of 1 year, 60% of the patients achieved MMR at 12 months while grade‐3/4 adverse events were reported in 23%; pleural effusions (all grade‐1/2) were reported in only 8%.…”
Section: Imatinib (Gleevec®) Dasatinib (Sprycel®) Nilotinib (Tasigna®...mentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, over the past decade, we have learned that dasatinib 50 mg daily is safer and as effective as 100 mg daily [ 30 , 31 , 81 ]. Bosutinib side-effects can be mitigated with a dose-escalation schedule: 100 mg daily x 1-2 weeks, then 200 mg daily x 2–4 weeks, then 300 mg daily x 1 month, then adjust the dose to 400 mg daily (approved dose in frontline therapy) or a lower or higher dose (500 mg daily; approved in subsequent-line therapies) depending on the response, CML status (frontline or later lines) and side-effects [ 82 , 83 ].…”
Section: Management Of CML Post-tki Toxicitiesmentioning
confidence: 99%